Measuring how healthcare organizations respond after patients experience harm: perspectives and next steps - Sokol-Hessner, Lauge; Adams, John; Hemmelgarn, Carole; Miller, Beth; O'Connor, Diane; Parkerton, Melissa; Schweitzer, Leilani; Austin, J. Matthew (Frontiers in Health Services, 2025)
Patients can experience serious harm from healthcare, the impacts can be prolonged, and events may also affect families and clinicians. Communication and Resolution Programs (CRPs) are designed to reduce these negative impacts, rebuild trust, and improve patient safety, but are not consistently implemented. To inform implementation efforts, enable accountability, and promote innovation, it is critical to develop standardized performance measures assessing CRPs’ structure, process, and outcomes. To advance CRP measurement, an interdisciplinary workgroup from the Pathway to Accountability, Compassion, and Transparency (PACT) Leadership and Innovation Network—a group of leading healthcare organizations with CRPs—explores meaningful approaches to measurement and proposes a set of next steps. Interested parties in CRP measurement prioritize developing person-centered outcome and experience measures; assessing equity; addressing clinician and organization concerns about how CRP measurement may affect reputational and legal risk; reducing the burden of measurement; and improving mechanisms for sharing data across organizations to promote transparency, accountability, and broader patient safety improvements. Recommended next steps include: build a national coalition of interested parties to guide the work; overcome barriers to measurement and improve feasibility, especially through the engagement of patient safety and risk management software vendors; explore measure development processes that focus on patient, family, and clinician-centered outcome and experience measures; define nationally recognized standardized CRP measures; consider the role for regulatory and financial incentives to promote their use; and facilitate data sharing and comparative analysis. Ongoing engagement and strategy will be essential to move CRP measurement forward.